(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2016)
The experiment was conducted in the experimental area of Sher-e-Bangla Agricultural University, Sher-e-Bangla Nagar, Dhaka during March to June, 2014 to study the genetic variability, correlation and path co-efficient analysis for yield and yield contributing characters of maize. In this experiment 25 maize genotypes were used as experimental materials. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. Mean performance, variability, correlation matrix and path analysis on different yield contributing characters and yield of maize genotypes were estimated. The highest grain yield/plant (272.21 g) was recorded in the genotype of BARI Hybrid Maize-6, whereas the lowest grain yield/plant (180.40 g) from the genotype of NZ-003. Phenotypic coefficient of variation was higher than the genotypic coefficient of variation for all the yield contributing traits. In correlation study, significant positive association was recorded for grain yield/plant of maize genotypes with plant height (0.235), tassel height (0.359), number of grains/cob (0.854), cob length (0.390), cob diameter (0.313) and weight of 1000-grains (0.689). Path analysis revealed that days to initiation of male flower had positive direct effect (0.132), days to initiation of female flower had negative direct effect (-0.254), days to maturity had positive direct effect (0.178), plant height had positive direct effect (0.314), tassel height had positive direct effect (0.234), ear length had positive direct effect (0.197), number of grains/cob had negative direct effect (-0.095), cob length had positive direct effect (0.167), cob diameter had positive direct effect (0.168) and that weight of 1000-grains had positive direct effect (0.217) on yield / plant.